PERSEPSI PEMULUNG TERHADAP ASPEK KESEHATAN KESELAMATAN KERJA (K3) DALAM PENGELOLAAN SAMPAH DI TEMPAT PEMBUANGAN SEMENTARA (TPS) KOTA PEKANBARU - Ridha Faisal Ridha Faisal; Suyanto "; Miftah Azrin (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2016)
ABSTRACTScavenger is a worker who sort the waste and has a high risk for disease and accident. It was caused by the waste in the garbage which mixed between organic waste and anorganic waste. However, they aren’t aware about that. One of the procedure to avoid that risk is using the Personal Protective Equipment (PPE).The aim of this study is to know perception of scavengers about occupational health and safety, and Personal Protective Equipment (PPE). The type of this study is descriptive qualitative approach with in-depth interviews, focus group discussions and observation. Sample of this study are 10 scavengers and divided into 2 groups : 4 scavengers for in-depth interview and 6 scavengers for focus group discussion. This study showed that the perception of scavengers about the risk of disease at working was bad, they only knew that weary and dizzy was caused by tired after working. Meanwhile, the perception of accident risk at working was good because they knew that the risk of injuries was caused by sharp object such as glass, knife or thorns and moving equipment such as bulldozer or trucks carrying waste. They only used gloves, safety shoes like booth and hat to reduced the risk and they didn’t use the mask because they thought that it interfered their inhalation.Keywords: Scavenger, Perception, Occupational Health and Safety, Personal Protective Equipment